Study Literatur Review: Faktor-Faktor yang Berpengaruh terhadap Audit Delay - Heri Heri; Carmel Meiden (AKUNTANSI 45, 2024)
This study aims to analyze what factors can influence the publication of financial reports or what is often called audit delay. The population in this research is Systematic Literature Review (SLR) articles where researchers studied or reviewed 20 (twenty) articles from 200 (two hundred) journals in the Google Scholar database for the year 2020-2023. The concept of this literature review uses the Auditor's Signature Lag and Preliminary Lag. The method used in this research is the literature review method. The literature review method is used to research, review, identify, and interpret all existing research on unique and interesting phenomenon topic areas, with certain relevant research questions. Based on the research results, it shows that there are factors that influence audit delay. So it can be concluded that the audit delay variable is a dependent variable that can be influenced by certain factors.